Pignot, Manon y Anne Tournieroux (eds.), Enfants en guerre, guerre à l’enfance? De 1914 à nos jours, Paris, Anamosa, 2024, 231p. ISBN: 978-2-38191-096-3. 35€ - Paola Ruiz-López (Memoria y Civilización)
Book Review